GEMC1 is a critical regulator of multiciliated cell differentiation. (1st March 2016) - Terré, Berta; Piergiovanni, Gabriele; Segura‐Bayona, Sandra; Gil‐Gómez, Gabriel; Youssef, Sameh A; Attolini, Camille Stephan‐Otto; Wilsch‐Bräuninger, Michaela; Jung, Carole; Rojas, Ana M; Marjanović, Marko; Knobel, Philip A; Palenzuela, Lluís; et al.
Abstract: The generation of multiciliated cells (MCCs) is required for the proper function of many tissues, including the respiratory tract, brain, and germline. Defects in MCC development have been demonstrated to cause a subclass of mucociliary clearance disorders termed reduced generation of multiple motile cilia (RGMC). To date, only two genes, Multicilin ( MCIDAS ) and cyclin O ( CCNO ) have been identified in this disorder in humans. Here, we describe mice lacking GEMC1 ( GMNC ), a protein with a similar domain organization as Multicilin that has been implicated in DNA replication control. We have found that GEMC1‐deficient mice are growth impaired, develop hydrocephaly with a high penetrance, and are infertile, due to defects in the formation of MCCs in the brain, respiratory tract, and germline. Our data demonstrate that GEMC1 is a critical regulator of MCC differentiation and a candidate gene for human RGMC or related disorders. Synopsis: In addition to a role in DNA replicaion, Geminin‐like coiled‐coil containing protein 1 (GEMC1) interacts with E2F4/5‐DP1 and Multicilin to control transcriptional programs required for multiciliated cell (MCC) differentiation in mammals. GEMC1 is required for normal growth and fertility in mice. Multiciliated cells and sperm require GEMC1. GEMC1 interacts with E2F4/5‐DP1 and Multicilin. Multiciliated cells transcriptional programs are activated by GEMC1. GEMC1 is a candidate gene for human ciliopathies. Abstract : In addition to a role in DNA replicaion, Geminin‐like coiled‐coil containing protein 1 (GEMC1) interacts with E2F4/5‐DP1 and Multicilin to control transcriptional programs required for multiciliated cell (MCC) differentiation in mammals.